Prezi-based Learning Video: Learning Media Validity and Feasibility - Divayuda, I Putu Gede Bagus Tedja; Wibawa, I Made Citra; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2021)
This research was conducted based on students’ low attention toward the implementation of learning using powerpoint so that it made the students lack of understanding and it caused the repetitive explanation of learning materials delivered by educators. This research aimed to produce a learning video media product using Prezi for fifth grade elementary school students on the Environmental Theme of Sahabat Kita, a valid sub-theme of Environmental Preservation Efforts. The type of this research was research and development carried out using ADDIE model. In the Implementation Phase, the test of learning video media products involving students was not carried out due to the Covid-19 pandemic conditions. The method of data collection was in the form of an instrument. The subjects of this study were two content subjects and two learning media experts. The technique used in conducting data analysis on the validity test of learning video media using Prezi was the Mean formula, calculating the percentage of each subject, and the overall percentage formula for the subject. The results of subject content validity conducted by two subject content experts obtained a percentage of 94.53% with very good qualifications. The results of the validity of learning video media conducted by two learning media experts obtained a percentage of 95.83% with very good qualifications. Thus, it can be said that the learning video media using Prezi that has been developed is valid, so it is feasible to be used to support the learning process on the Environmental Theme of Sahabat Kita, the Sub-theme of Environmental Preservation for fifth grade elementary school students.